2014
DOI: 10.1021/nl503402c
|View full text |Cite
|
Sign up to set email alerts
|

Topographically-Designed Triboelectric Nanogenerator via Block Copolymer Self-Assembly

Abstract: Herein, we report a facile and robust route to nanoscale tunable triboelectric energy harvesters realized by the formation of highly functional and controllable nanostructures via block copolymer (BCP) self-assembly. Our strategy is based on the incorporation of various silica nanostructures derived from the self-assembly of BCPs to enhance the characteristics of triboelectric nanogenerators (TENGs) by modulating the contact-surface area and the frictional force. Our simulation data also confirm that the nanoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
187
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 323 publications
(195 citation statements)
references
References 78 publications
0
187
0
2
Order By: Relevance
“…Fan et al studied the influence of varies micro‐fabricated surface structures of PDMS on TENG's output, and found that the TENG with pyramid shaped surface structure can produced highest output compared with that with cubic or liner shaped surface structure 63. Recently, Zhao et al developed a very simple and rapid material surface processing method which can efficiently create liner structure on many friction films and result in an increased electrical output 64. Besides, surface charging and chemical modification for the friction material have also been proposed by researchers to not only improve the output performance of TENGs, but also increase their stability in various environmental conditions 65…”
Section: Materials and Device Designmentioning
confidence: 99%
“…Fan et al studied the influence of varies micro‐fabricated surface structures of PDMS on TENG's output, and found that the TENG with pyramid shaped surface structure can produced highest output compared with that with cubic or liner shaped surface structure 63. Recently, Zhao et al developed a very simple and rapid material surface processing method which can efficiently create liner structure on many friction films and result in an increased electrical output 64. Besides, surface charging and chemical modification for the friction material have also been proposed by researchers to not only improve the output performance of TENGs, but also increase their stability in various environmental conditions 65…”
Section: Materials and Device Designmentioning
confidence: 99%
“…Nanogenerators (NGs) are emerging as novel devices which can convert various kinds of ambient energy into electric power via piezoelectric,5 triboelectric,6, 7 or pyroelectric effect4 both in nanoscale and macroscale. As a typical piezoelectric nanomaterial, ZnO nanowire was found to demonstrate piezoelectric potential distributing along its c ‐axis when subjected to lateral bending or axial tension and compression, which is the basic mechanism of piezoelectric NGs 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, H 2 sensors, utilizing nanogap structures [10,11], surface acoustic wave (SAW) [13,14], Schottky diodes structure [15,16], and surface plasmon effect [17,18], have been reported. Recently, triboelectric energy harvesting has gained much attention as a route to supply necessary power to operate electronic devices [20,21,22,23,24,25,26]. Further, few attempts have been made to develop chemical sensors utilizing triboelectric effect [27,28].…”
Section: Introductionmentioning
confidence: 99%